The use of pineapple leaf fibres as an alternative yarn for songket motives / Norhidayu Yussoff - Yussoff, Norhidayu (2013)
Songket has its own aesthetic values. It depends on the materials used to make it. Among the most common materials are cotton threads, pineapple, banana, gold and silver. Once, people usually use songket that was made from cotton, pineapple, and banana, while those that are made from gold and silver thread are for royalties and aristocrats. This research was done to study the advantages of the pineapple fibre that can be made into thread and replaced the gold and silver thread in weaving. This research is also done to identify the suitable tools and materials to be used in ripping pineapple leaves to extract the fibre. Apart from that, it is done to identify the differences between natural coloured thread and chemical coloured one. Instruments that have been used in this study are interviews and observations. This interview was carried out by 3 respondents. All the data given based on the processes and the artwork. This is an experimental research using qualitative methods. The result of this study shows that pineapple fibre thread is very suitable to be used as motives in songket and can replace the gold or silver thread.